Pelatihan Penilaian Pembelajaran PAUD Bagi Orang Tua - Seran, Theodorina Novyani; Kale, Sartika; Koten, Angelikus Nama; Mundiarti, Vanida; Margiani, Kristin; Betty, Credo G. (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
The assessment conducted during the Covid-19 pandemic reflects the low knowledge and understanding of parents in assessing learning in ECCE. Learning that was originally in school was transferred to learning at home, which creates difficulties for parents, especially in relation to filling out assessment forms during the learning period at home, and most parents carry out subjective assessments during the learning period at home. The assessment from parents has not been based on the reality that happens to children, this will certainly have a major impact on the communication of children's learning assessment results. The purpose of this activity is to broaden parents' knowledge and understanding and balance parents' and teachers' opinions on ECCE learning assessment. The method used in this activity is an adult approach, specifically through training. There were 39 participants who participated in this activity. This training material explains how to assess learning in ECCE, how to create an assessment format, and how to complete the assessment format. The results of the test analysis showed that parents' knowledge and understanding of ECCE learning assessments increased by 53.33%. The participants' knowledge and comprehension score, which was initially 35.64%, increased to 89.48%. This indicates that this training was successfully carried out to increase parents' knowledge and understanding of ECCE learning assessment.